Three-Dimensional Characterization of the Anterior Cruciate Ligament's Femoral Footprint - Westermann, Robert; Sybrowsky, Christian; Ramme, Austin; Amedola, Annuziati; Wolf, Brian R. (The Journal of Knee Surgery, 2014)
There is increasing use of three-dimensional (3D) computed tomography (CT) for researching anterior cruciate ligament (ACL) reconstructions and tunnel placement. However, there is limited 3D CT data on the ACL footprint. The purpose of this study is to define the native ACL femoral footprint using 3D surface reconstructions of computed tomography (CT) imaging of cadaveric knees. The femoral insertion of the ACL was meticulously dissected and marked with drill holes in seven cadaveric knees. CT scans were performed on each specimen, and 3D computer models were created. Distance from the condyle edges to the margins of the footprint were referenced to the total condylar size. This was performed both parallel and perpendicular to the femoral axis as well as the intercondylar notch. The mean condylar depth (c/C) ratios along the axis of the femur were 0.45 ± 0.06 for the anterior border, 0.44 ± 0.08 for the posterior border, 0.26 ± 0.07 for the proximal border, and 0.63 ± 0.08 for the distal border. The mean notch (n/N) ratios for the four margins were 0.37 ± 0.04 for the anterior border, 0.67 ± 0.08 for the posterior border, 0.49 ± 0.07 for the proximal margin, and 0.50 ± 0.06 for the distal border. The mean c/C ratios parallel the intercondylar notch measured 0.23 ± 0.03 for the anterior border, 0.27 ± 0.04 for the posterior border, 0.37 ± 0.04 for the proximal border, and 0.12 ± 0.02 for the distal border. The mean n/N ratios perpendicular to the intercondylar notch measured 0.11 ± 0.06 for the anterior border, 0.52 ± 0.09 the posterior border, 0.29 ± 0.06 for the proximal border, and 0.30 ± 0.06 for the distal border. This study provides reference measures of the femoral footprint of the ACL using 3D CT. It will assist future studies that use advanced imaging to evaluate accuracy of ACL reconstruction.
Keywords: ACL; footprint; knee; femur; insertion